Degradation of the oxide film formed on Alloy 690TT in a high-temperature chloride solution - Hou, Qiang; Liu, Zhiyong; Li, Chengtao; Li, Xiaogang; Shao, Jiamin (Applied surface science, 2019)
[Display omitted] •A monolayer oxide film with several little corrosion pits on Alloy 690TT is formed.•The film formed in a Cl−-containing solution mainly consist of NiCr2O4 and Cr(OH)3.•The adsorption of Cl− can cause the enhanced locally dissolution of Ni-rich oxides. Comparative analyses are adopted to examine the influences of Cl− on the degradation of the film on Alloy 690TT in high-temperature water. According to the results of surface analyses and TEM, the composition and structure of the oxide film formed in a chloride solution are determined. Unlike the duplex layer oxide film formed on the sample in pure water, a thinner and monolayer Cr-rich oxide scale with several little corrosion pits on the surface is formed, which is closely related to the adsorption of Cl− ions due to their affinity to material surface and the selective dissolution of Ni-rich oxides.